Crise hídrica e incêndios florestais no Pantanal de Mato Grosso : um olhar para o ensino de geografia - Carvalho, Robson Ferreira da Silva (2024)
This research proposes a discussion about the water crisis and forest fires that occurred in the Pantanal of Mato Grosso, exploring how these topics are addressed in the National Common Curricular Base (BNCC) and the Educational Guidelines of the State of Mato Grosso (DRCsMT), and suggesting ways to develop them in Geography teaching. Using a qualitative approach, documentary research and analysis of bibliographic sources and journals focusing on the events of 2020 were conducted. The investigation revealed the deficiencies and potentialities of public education policies regarding the inclusion of water crisis and forest fires topics. A broad debate was promoted to understand the relationship between these phenomena in the Pantanal of Mato Grosso and the importance of Geography teaching for the understanding and prevention of these events. Geography is highlighted as fundamental for active and transformative understanding of reality, going beyond mere data repetition. By examining issues such as water scarcity and fires, the research emphasizes the connection between human actions and environmental impacts, advocating for a joint and integrated approach. Innovative pedagogical strategies were proposed, such as using satellite images from Google Earth and exploring educational podcasts, to address the topics in a more engaging and contextualized manner. The analysis also highlighted the importance of methods like films and specific lesson plans to foster environmental and geographical education among students.